A Structural Model of the Influence of Artificial Intelligence Use and Self-Efficacy on Communication Skills Through Critical Thinking Among Economics Education Students at the Faculty of Economics and Business, University of Yogyakarta - Aprillia Dwi Handayani; Ahmad Hafidh Saiful Fikri (International Journal of Economic and Business Research, 2026)
This study examined the structural relationships among Artificial Intelligence use, self efficacy, critical thinking, and communication skills among undergraduate students of the Economics Education Program at the Faculty of Economics and Business, Yogyakarta State University. The study employed a quantitative explanatory approach using an ex post facto design. Data were collected from 249 students through a structured questionnaire based on a five point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling. The findings revealed that Artificial Intelligence use and self efficacy significantly and positively influenced critical thinking. Artificial Intelligence use, self efficacy, and critical thinking also demonstrated significant positive effects on communication skills. Critical thinking emerged as the strongest predictor of communication skills and functioned as a significant mediating variable in the relationships between Artificial Intelligence use and communication skills as well as between self efficacy and communication skills. The results indicate that the effectiveness of Artificial Intelligence in higher education depends not only on technological utilization but also on students’ cognitive capabilities in evaluating, interpreting, and communicating information. The study highlights the strategic importance of integrating Artificial Intelligence supported learning environments with initiatives that strengthen self efficacy and critical thinking to improve students’ academic communication competence.